Análise da Capacidade Absortiva de áreas de negócio da Ambev nas interações de Inovação Aberta com startups - Helaindo Guimarães Júnior (2022)
The open innovation scenario has been growing and being the subject of studies in relation to interactions between companies and external actors to generate innovation and competitive advantage. The present work aims to analyze the concept of Absorptive Capacity in Open Innovation relationships with startups by business areas of Ambev. The discussion evaluates the business context of the multinational ABInBev and the subsidiary Ambev in their intra-company networks. As well as the role of the internal innovation area and the business areas so that interactions with startups are executed and managed. For this, a quantitative and qualitative research methodology was designed that made it possible to identify how the company relates to startups and analyze the Absorptive Capacity of business areas prioritized in this process. With this, the result of the analysis can classify the areas in different levels of maturity and suggest proposals for improving the processes involved to improve the Absorptive Capacity in each of them. In addition, propositions related to organizational aspects, in general, and suggestions for the internal open innovation area are part of the conclusion of the work.